ANALISIS KINERJA GURU BK: PELAKSANAAN BIMBINGAN KLASIKAL DI SEKOLAH MENENGAH KEJURUAN - Rihya Syifa Qurrotu Ayuna; Farah Wahyuni; Happy Karlina Marjo (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
This study aims to look at the performance of guidance and counseling teachers at SMKN 1 Cikarang Utara in the 2023/2024 academic year. This research uses a type of qualitative research with a case study design with a focus on developing an in-depth analysis of the performance of guidance and counseling teachers. Data collection techniques using observation of the environment of SMKN 1 Cikarang Utara, interviews with the head of bk coordination and 3 guidance and counseling teachers and documentation in the form of photos and collection of supporting data. Data validity techniques use validity and credibility tests by triangulation as reinforcement and supporting data. The results showed that the implementation of the classical guidance  program carried out went well in accordance with the objectives to be achieved. There is a change for the better in achieving service goals before and after being given a classical guidance program. These changes were accepted by several students. Changes that occur include changes in behavior, mindset, insight and knowledge.